2008
DOI: 10.1007/s11293-007-9104-8
|View full text |Cite
|
Sign up to set email alerts
|

The Ex-Dividend Day Stock Price Behavior: The Case of Portugal

Abstract: Ex-dividend day, Tax clientele, Tick price, Stock price drop, G20 Financial Markets and Institutions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 36 publications
3
13
1
1
Order By: Relevance
“…Hasil ini juga didukung oleh pengujian yang menunjukkan terdapat perbedaan proporsi yang signifikan antara sampel yang mengalami penurunan harga saham dengan sampel Hasil tersebut dapat menunjukan bahwa dividen masih menjadi pertimbangan investor di Bursa Efek Indonesia untuk berinvestasi di instrumen saham. Hasil ini juga sejalan dengan hasil penelitian terdahulu yang membuktikan bahwa harga saham jatuh lebih kecil dari besarnya dividen pada ex-dividend date (Elton & Gruber, 1970;Kalay 1982;Yahyaee et al, 2008;Borges, 2008). Turunya dividen tersebut sebenarnya juga dapat dijelaskan melalui Bird-in-the-hand theory yang menyatakan bahwa investor lebih menyukai dividen dibandingkan capital gain dengan anggapan bahwa dividen lebih pasti dibandingkan capital gain sehingga dividen sangat cocok untuk investor yang kebanyakan bersifat risk averse.…”
Section: Pembahasanunclassified
“…Hasil ini juga didukung oleh pengujian yang menunjukkan terdapat perbedaan proporsi yang signifikan antara sampel yang mengalami penurunan harga saham dengan sampel Hasil tersebut dapat menunjukan bahwa dividen masih menjadi pertimbangan investor di Bursa Efek Indonesia untuk berinvestasi di instrumen saham. Hasil ini juga sejalan dengan hasil penelitian terdahulu yang membuktikan bahwa harga saham jatuh lebih kecil dari besarnya dividen pada ex-dividend date (Elton & Gruber, 1970;Kalay 1982;Yahyaee et al, 2008;Borges, 2008). Turunya dividen tersebut sebenarnya juga dapat dijelaskan melalui Bird-in-the-hand theory yang menyatakan bahwa investor lebih menyukai dividen dibandingkan capital gain dengan anggapan bahwa dividen lebih pasti dibandingkan capital gain sehingga dividen sangat cocok untuk investor yang kebanyakan bersifat risk averse.…”
Section: Pembahasanunclassified
“…However, the market can be less efficient. Since an efficient market hypothesis is a simplified theoretical approach based on fundamental assumptions, which can be violated -as shown in previous studies (Borges, 2009;Mallikarjunappa & Manjunatha, 2009;Vazakidis & Athianos, 2010), it is important to assume that the possibility to get abnormal returns exists and the width of event window used in the research helps to represent those expectations of the possible market inefficiency. Hence, the more inefficient the market is expected to be, the wider the event window that should be used.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies, which report weak efficiency of the market, are rather broad. Borges (2009) examined the ex-dividend day behavior of stock prices in the Lisbon Stock Market (Portugal) over the period 1990-1998 using 446 observations from 121 firms. This study found that on the ex-day stock prices fall by the amount less than the dividend, which could be treated as an anomaly thus reflecting a less than efficient market with low liquidity levels, price stickiness, and insipid arbitrage trading.…”
Section: An Overview Of the Literature On Dividend Policy's Impact Onmentioning
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature dividend policies and their impact of stock prices mostly discussed in the context of signalling theory and efficient market hypothesis, however over the last decade researchers have started to investigate if those theories are still relevant and if the other theories such as agency and behavioral theories may be the better theoretical frameworks to explain the movements of stock price (Legenzova et.al, 2017). There are many studies in the previous literature investigating the effect of dividend announcements on stock prices (Borges, 2009;Dasilas and Leventis, 2011;Sulaiman and Migiro, 2015). Even though previous literature regarding stock prices' reaction to dividend announcements is rather broad, there are still few studies analyzing the effect of football club dividend announcements 9th Istanbul Finance Congress (IFC -2020), Vol.12-p.31-34 Kevser, Dogan _____________________________________________________________________________________________________ DOI: 10.17261/Pressacademia.2020.1343 32 PressAcademia Procedia on stock returns in the context of Turkey.…”
Section: Introductionmentioning
confidence: 99%